2019
DOI: 10.1158/1078-0432.ccr-18-4024
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Is Overexpressed in BRCA1-like Breast Tumors and Predictive for Sensitivity to High-Dose Platinum-Based Chemotherapy

Abstract: Purpose: BRCA1-deficient breast cancers carry a specific DNA copy-number signature ("BRCA1-like") and are hypersensitive to DNA double-strand break (DSB) inducing compounds. Here, we explored whether (i) EZH2 is overexpressed in human BRCA1-deficient breast tumors and might predict sensitivity to DSB-inducing drugs; (ii) EZH2 inhibition potentiates cisplatin efficacy in Brca1-deficient murine mammary tumors. Experimental Design: EZH2 expression was analyzed in 497 breast cancers using IHC or RNA sequencing. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…Tazemetostat, an EZH2 inhibitor, has been approved for treating epithelioid sarcoma, and it is the first EZH2 inhibitor approved by FDA [47]. Other EZH2 inhibitor, GSK343 and GSK236, were also reported to inhibit tumor progression in various cancer, such as glioblastoma [48], head and neck cancer, [49] and breast cancer [50]. Our in vitro study confirmed the regulatory mechanism of miR-33a/EZH2 cascade in TNBC progression, thus, more investigation of the effects of miR-33a and EZH2 on tumor growth and metastasis in vivo is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Tazemetostat, an EZH2 inhibitor, has been approved for treating epithelioid sarcoma, and it is the first EZH2 inhibitor approved by FDA [47]. Other EZH2 inhibitor, GSK343 and GSK236, were also reported to inhibit tumor progression in various cancer, such as glioblastoma [48], head and neck cancer, [49] and breast cancer [50]. Our in vitro study confirmed the regulatory mechanism of miR-33a/EZH2 cascade in TNBC progression, thus, more investigation of the effects of miR-33a and EZH2 on tumor growth and metastasis in vivo is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of BRCA activity can occur by somatic or germline mutation, loss of heterozygosity, copy number alterations (regional or whole chromosome alterations or deletions), or promoter methylation with gene silencing [59,60]. Multiple investigators have demonstrated that BRCA gene silencing via hypermethylation occurs not only in AML but also in multiple solid tumors, including breast, ovary, and prostate cancer [56,57,[59][60][61][62][63][64]. In addition, hypermethylation has been reported as a consequence of both cytotoxic chemotherapy and radiation [58].…”
Section: Hrd and T-mds/amlmentioning
confidence: 99%
“…EZH2 is the catalytic subunit of the PRC2, which functions together with Embryonic Ectoderm Development (EED) and Suppressor of Zeste 12 (SUZ12) as a histone methyltransferase to silence areas of active transcription through H3K27me3. EZH2 is an oncogene that is overexpressed in many cancer types, including SCLC [ 9 - 11 ], and high EZH2 expression is correlated with tumorigenesis, cancer progression, metastasis, and poor prognoses [ 10 , 12 - 19 ]. As such, EZH2 has emerged as an important therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…A role for EZH2 in genome maintenance has previously been described. EZH2 has been reported to mediate resistance to DNA damaging agents, including etoposide in SCLC [ 34 - 37 ] and cisplatin in several other cancer cell types [ 9 , 38 - 41 ], localize to DNA damage sites [ 42 , 43 ], and promote DNA double-strand break (DSB) repair [ 42 , 44 ], degradation of stalled replication forks [ 45 ], and checkpoint signaling [ 46 ]; however, these functions have largely been attributed to H3K27Me3, either through transcriptional repression or a recently-described function for H3K27Me3 in the recruitment of MUS81 [ 45 ]. Significantly, a role for EZH2 in promoting NER, as well as in promoting genome maintenance independent of its catalytic activity or PRC2, has previously not been shown.…”
Section: Introductionmentioning
confidence: 99%